Formulation and evaluation of microemulsion-based hydrogel for topical delivery - Sabale, Vidya; Vora, Sejal (International Journal of Pharmaceutical Investigation)
Background: The purpose of this study was to develop microemulsion-based hydrogel formulation for topical delivery of bifonazole with an objective to increase the solubility and skin permeability of the drug. Materials and Methods: Oleic acid was screened as the oil phase of microemulsions, due to a good solubilizing capacity of the microemulison systems. The pseudo-ternary phase diagrams for microemulsion regions were constructed using oleic acid as the oil, Tween 80 as the surfactant and isopropyl alcohol (IPA) as the cosurfactant. Various microemulsion formulations were prepared and optimized by 32 factorial design on the basis of percentage (%) transmittance, globule size, zeta potential, drug release, and skin permeability. The abilities of various microemulsions to deliver bifonazole through the skin were evaluated ex vivo using Franz diffusion cells fitted with rat skins. The Hydroxy Propyl Methyl Cellulose (HPMC) K100 M as a gel matrix was used to construct the microemulsion-based hydrogel for improving the viscosity of microemulsion for topical administration. The optimized microemulsion-based hydrogel was evaluated for viscosity, spreadability, skin irritancy, skin permeability, stability, and antifungal activity by comparing it with marketed bifonazole cream. Results: The mechanism of drug release from microemulsion-based hydrogel was observed to follow zero order kinetics. The studied optimized microemulsion-based hydrogel showed a good stability over the period of 3 months. Average globule size of optimized microemulsion (F5) was found to be 18.98 nm, zeta potential was found to be -5.56 mv, and permeability of drug from microemulsion within 8 h was observed 84%. The antifungal activity of microemulsion-based hydrogel was found to be comparable with marketed cream. Conclusion: The results indicate that the studied microemulsion-based hydrogel (F5) has a potential for sustained action of drug release and it may act as promising vehicle for topical delivery of ibuprofen.
Keywords: Antifungal activity; bifonazole; oleic acid; permeability; phase diagram; zeta potential